The Effect of Organisational Culture, Work Environment and Training on Employee Job Satisfaction (a Study at Otika Medika Hospital, Serang Regency) - Yoki Adam; Mahsoca Hera Fermana; Dede Sonaji; John Chaidir; Haerofiatna Haerofiatna (Jurnal Manajemen, Akuntansi, Ekonomi, 2026)
This study aims to analyze the influence of organizational culture, work environment, and training on employee job satisfaction at Otika Medika Hospital in Serang Regency. This research employed a quantitative approach using a survey method. Data was collected through questionnaires distributed to hospital employees who served as research respondents. The sampling technique used probability sampling. Data analysis was conducted using multiple linear regression analysis with the assistance of statistical software to examine the effect of independent variables on the dependent variable. The results of the study indicate that organizational culture, work environment, and training partially have a positive and significant effect on employee job satisfaction. Furthermore, the simultaneous test results show that these three variables collectively have a significant influence on employee job satisfaction. The findings suggest that strengthening positive organizational culture, creating a conducive work environment, and implementing effective training programs can enhance employee satisfaction. Therefore, organizations need to pay attention to managing organizational culture, improving the work environment, and developing employee competencies through sustainable training programs to improve job satisfaction and organizational performance